EMOTIONS IN HUMANS - S, NITHYA; Rau, S. S. (International Journal of Psychosocial Rehabilitation, 2020)
Emotions in humans are being defined in different perspective by different researchers all over the world. Say, researchers in biological field have defined emotions as electro-chemical reactions and psychology based researchers have defined emotions as conscious experience. Whereas most of the people who study emotions as a coordinated response system convey that emotion occurs when certain biological, experienced and cognitive states occur simultaneously. Thus, the current paper focuses on emotions from an Ayurvedic and Vedic psychological perspective taking consciousness as a base.